2020
DOI: 10.1177/1082013220935224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anise (Pimpinella anisum L.) essential oil on the microbial, chemical, and sensory properties of chicken fillets wrapped with gelatin film

Abstract: The present study aimed to develop a novel active edible film based on gelatin incorporated with 0, 0.3, 0.6, and 0.9% w/w anise essential oil as a natural preservative and investigate the shelf life extension potential of chicken fillets during 12 days of refrigerated storage. The chicken fillets were wrapped with the essence-free and anise essential oil-loaded gelatin films, and microbial counts, chemical and sensory tests were surveyed during chilled storage. Results showed that aerobic mesophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…Similar to the results of the current study, Fitsiou et al 77 studied the essential oils of several medicinal plants and found that the P. anisum essential oil did not have any antibacterial activity. On the contrary, there were reports of antibacterial properties of the essential oil of this plant on the same bacteria, MIC in the range of 0.06 to 0.25 µg/mL 78 and 2.0 to 3.0 µg/mL 60 were reported, which were inconsistent with the results of this study.…”
Section: Resultscontrasting
confidence: 99%
“…Similar to the results of the current study, Fitsiou et al 77 studied the essential oils of several medicinal plants and found that the P. anisum essential oil did not have any antibacterial activity. On the contrary, there were reports of antibacterial properties of the essential oil of this plant on the same bacteria, MIC in the range of 0.06 to 0.25 µg/mL 78 and 2.0 to 3.0 µg/mL 60 were reported, which were inconsistent with the results of this study.…”
Section: Resultscontrasting
confidence: 99%
“…Initial meat contamination can be caused by contact with skin, feet, and intestinal contents of the animal, and so on, during processing, and degree of initial contamination shows the degree of meat processing hygiene (Satin, 2002). As shown in Table 2, in control sample, increasing trends of different extents were observed in all treatments of TG1, which was significantly ( p < 0.05) dependent on the storage time and the addition of AEO concentration and, in agreement with previous studies (Fathi‐Achachlouei et al., 2021; Hamedi et al., 2017; Shavisi et al., 2017). Results showed that TVC of control, PLA‐0, and PLA‐0.6 treatments of TG1 (7.72, 7.35, and 7.07 log CFU/g, respectively) exceeded 7 log CFU/g as acceptable TVC limit for meat quality reported by Ercolini et al.…”
Section: Resultssupporting
confidence: 90%
“…Active packaging can be considered a new technique to improve food safety and quality by inhibiting the microbial growth in food via the gradual release of antimicrobial compounds into the food (Appendini & Hotchkiss, 2002; Fathi‐Achachlouei et al., 2021; Yin et al., 2023). Biobased polylactic acid (PLA), which is made from agricultural resources such as corn, is one of the interesting aliphatic polyester polymers and can be used instead of petroleum‐based polymers due to the its useful physical and mechanical characteristics (Mascheroni et al., 2010; Rhim et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors stated that the meat of chicken drumsticks fed with oregano essential oil was much juicier compared to the meat of drumsticks of control broiler chickens and chickens to which antibiotics had been added; they also stated that oregano essential oil significantly improved the appearance of drumstick meat compared to antibiotic-fed chicken meat [179]. The positive effect of essential oils on the sensory properties of chicken meat has been proven in many other studies [101,166,180,181].…”
Section: Influence Of Essential Oils On Broiler Chickens' Meat Qualitymentioning
confidence: 91%